Challenges in implementing dengue surveillance in Bantul District Special Region of Yogyakarta, Indonesia - Astuti, Fardhiasih Dwi; Widyaningsih, Vitri; Pamungkasari, Eti Poncorini; Subijanto, Achmad Arman (International Journal of Public Health Science (IJPHS), 2025)
The surveillance system is a source of information for policymaker to address the dengue outbreak. However, there was a lack of information on the effectiveness of dengue surveillance system in reporting the outbreak. This study aims to assess dengue surveillance activities in Bantul District, Special Region of Yogyakarta, Indonesia, one of the districts with a high burden of dengue, to provide information on current effectiveness and need assessment for further improvement for dengue surveillance system. This qualitative study was conducted in Bantul District, Special Region of Yogyakarta. The assessment approach was based on the input-processoutput-outcome (IPOO) model. The study participants were selected based on purposive sampling. Data were collected through interviews. Eight program holder surveillance were interviewed based on the interview guide. The surveillance system in Bantul Regency already utilizes electronic reporting. Reporting cases of dengue uses the system for surveillance of outbreak events (SISKLB). Analysis and interpretation are done to monitor progress in cases. The follow-up evaluation ceses is vector control to prevent the spread of the case. The incidence of dengue is still higher than the national rate. The case fatality rate (CFR) for dengue is <1%; CFR has hit its target. The larvae-free rate hasn't reached its target yet. Optimizing electronic reporting can improve the quality of information used as a reference in decision-making. SISKLB was created for timely reporting and monitoring of dengue cases. Monitoring available data laboratory can be used as a quick response to take action to prevent an increase in cases.